1990
DOI: 10.1070/qe1990v020n08abeh007148
|View full text |Cite
|
Sign up to set email alerts
|

Leakage currents and 1/fnoise in buried InGaAsP/InP heterostructure lasers

Abstract: A simple method for increasing the thermal efficiency of shape bimorph electrothermal micro-actuators is proposed, based on a reduction of gas conduction cooling beneath the hot arms by a deep, localized undercut. A single-sided, single-mask SCREAM-type process for fabricating differentially cooled actuators in a bonded silicon-on-insulator material is demonstrated. The process uses deep reactive ion etching and undercut to form suspended parts and isotropic reactive ion etching and lift-off of sacrificial shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Whereas several studies reported a strong correlation between optical noise (either frequency or intensity noise) and terminal voltage noise [32][33][34][35][36] as we observed here for mid-infrared QCLs, some others, on the contrary, assessed the absence of any cor-relation between these two quantities [37]. The origin of 1/f noise in near-infrared semiconductor light sources has also been largely discussed in various devices including laser diodes at 0.8 [37], 1.3 [38] and 1.55 μm [32,35], but also in superluminescent diodes [39]. Different poten-tial explanations have been suggested about the origin of flicker noise, such as the appearance of some sort of cur-rent fluctuations due to the presence of carrier traps in the vicinity of the active region, perhaps related to strains resulting from lattice mismatch close to the heterojunc-tion interfaces [37], or induced by different types of non-radiative carrier recombination such as surface and inter-face recombination or recombination at deep levels [35].…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Whereas several studies reported a strong correlation between optical noise (either frequency or intensity noise) and terminal voltage noise [32][33][34][35][36] as we observed here for mid-infrared QCLs, some others, on the contrary, assessed the absence of any cor-relation between these two quantities [37]. The origin of 1/f noise in near-infrared semiconductor light sources has also been largely discussed in various devices including laser diodes at 0.8 [37], 1.3 [38] and 1.55 μm [32,35], but also in superluminescent diodes [39]. Different poten-tial explanations have been suggested about the origin of flicker noise, such as the appearance of some sort of cur-rent fluctuations due to the presence of carrier traps in the vicinity of the active region, perhaps related to strains resulting from lattice mismatch close to the heterojunc-tion interfaces [37], or induced by different types of non-radiative carrier recombination such as surface and inter-face recombination or recombination at deep levels [35].…”
Section: Discussionmentioning
confidence: 43%
“…A link between the level of frequency noise and the behavior of the laser differential resistance was previously reported in semiconductor laser diodes and was explained in terms of leakage currents [38]. Based on this observation, low-frequency 1/f noise has been proposed as a sensitive measure of the quality and reliability of near-infrared laser diodes [32,36], by indicating the presence of intrinsic defects or fabrication imperfections that can act as deep traps or recombination centers in the semiconductor structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work seems to reinforce this idea by showing a connection between deviations from ideal diode I-V performance (due to leakage currents) and 1/f noise in buried heterostructure lasers [1,11]. Therefore, depending on the magnitude of the leakage current of the SCOWECL, a reduction of the 1/f noise by approximately a factor of 3 would not be unreasonable.…”
Section: Appendix C Directions For Future Research: Reducing the 1/f mentioning
confidence: 95%
“…Unfortunately, the precise origin of the 1/f noise is not well understood theoretically. However there are several documented sources such as fluctuations from leakage currents within the buried heterostructure device, carrier traps caused by dangling bonds at the cleaved laser facets, and mode competition noise [9][10][11][12]. Despite this uncertainty, the magnitude of the 1/f noise in commercially available semiconductor lasers has decreased dramatically over the years with the introduction of ECSLs that have been optimized for lower chirp and reduced leakage current [1,2].…”
Section: Theoretical Backgroundmentioning
confidence: 99%